Pharmacognosy Research - Indexed on PubMed Central - Ambrose Furey (Pharmacognosy Research, 2011)
I am delighted to bring you the good news that our journal Pharmacognosy Research is now indexed on PubMed Central (PMC) and on the PubMed list. This is a wonderful achievement and a tribute to the hard work and dedication of all our editorial board members most especially the trojan work of our Managing Editor Prof. Muneen Ahmed KK. Read More ...
Keywords: Nil